Oxide 2D electron gases as a route for high carrier densities on (001) Si - Kornblum, Lior; Jin, Eric N.; Kumah, Divine; Ernst, Alexis T.; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2015)
Two dimensional electron gases (2DEGs) formed at the interfaces of oxide heterostructures draw considerable interest owing to their unique physics and potential applications. Growing such heterostructures on conventional semiconductors has the potential to integrate their functionality with semiconductor device technology. We demonstrate 2DEGs on a conventional semiconductor by growing GdTiO3-SrTiO3 on silicon. Structural analysis confirms the epitaxial growth of heterostructures with abrupt interfaces and a high degree of crystallinity. Transport measurements show the conduction to be an interface effect, ∼9 × 1013 cm-2 electrons per interface. Good agreement is demonstrated between the electronic behavior of structures grown on Si and on an oxide substrate, validating the robustness of this approach to bridge between lab-scale samples to a scalable, technologically relevant materials system. © 2015 AIP Publishing LLC.
Keywords: D electrons; Degree of crystallinity; Electron gas; Electronic behaviors; Heterojunctions; Interface effect; Materials systems; Oxide heterostructures; Oxide substrates; Semiconducting silicon; Semiconductor devices; Silicon; Transport measurements; Two dimensional electron gas; dept.phy

Combinatorial exploration of color in gold-based alloys - Liu, Jingbei; Liu, Yanhui; Gong, Pan; Li, Yanglin; Moore, Kimberly M.; Scanley, Ellen; Walker, Fred; Broadbridge, Christine; Schroers, Jan (Gold Bulletin, 2015)
Combinatorial approaches comprised of combinatorial magnetron co-sputtering deposition and fast screening methods are introduced to study color as a function of composition in Au-based alloys. The microstructures of the thin films and bulk alloys are identified by X-ray diffraction, and their colors of the alloys are characterized by optical reflectivity. The results reveal that when comparing microstructures and reflectivity, thin films are similar to bulk alloys. In Au-Ag-Cu solid solutions, the color of the ternary alloy follows the rule of mixture. For colors resulting from AuAl2 intermetallic, the color of an alloy scales with the percentage of the intermetallic phase and the deviation from its ideal binary composition. In the Au-Al-Cu library, we found a ∼90 % AuAl2 area fraction compositional window where copper addition can be tuned to improve mechanical properties while keeping purple color, even though Al and CuAl2 phases exist. Moreover, when comparing the color in Au-Cu-Si-Ag amorphous and crystalline state solid solution for the same composition, the colors are essentially identical. © 2015 The Author(s).
Keywords: Aluminum; Amorphous alloys; Amorphous silicon; Amorphousalloys; Binary composition; Color; Combinatorial approach; Crystalline materials; Crystalline state; Decorative thin film coating; Decorative thin films; Gold; Gold alloys; Gold based alloys; Gold coatings; Intermetallic phase; Intermetallics; Magnetron co-sputtering; Magnetrons; Microstructure; Optical reflectivity; Reflection; Silver; Silver alloys; Solid solution; Solid solutions; Thin films; X ray diffraction; dept.phy